Effect of hot air assisted infrared drying on drying characteristics and quality of rice bran pellets - Sahachart Sansak; Jiraporn Sripinyowanich Jongyingcharoen (My University, 2018)
The objective of this study was to determine drying characteristics and quality of rice bran pellet subjected to hot air assisted infrared (HA-IR) drying at different levels of infrared (IR) intensity (750 – 3750 W/m 2 ) and air temperature (40 – 80°C). The rice bran pellets were dried from 0.18 to 0.08 g water/g dry matter. The maximum drying rate (DR) and drying time were in the ranges of 0.0030 – 0.0165 g water/g dry matter·min and 8 – 54 min, respectively. Higher IR intensity and air temperature resulted in greater maximum DR and shorter drying time. The same trend was also observed for the effective moisture diffusivity (D eff ) values which were between 0.3103×10 -7 and 2.7603×10 -7 m 2 /s. As compared to the commercial reference sample of dried rice bran pellets, the products of this study had higher oil content and lower FFA content. The oil content was affected by IR intensity only while the FFA content was affected both by IR intensity and air temperature. HA-IR drying could improve drying characteristics of the rice bran pellets and produce better quality of the dried products.
Keywords: Pellet; Food Drying and Modeling